Implementation of Border Tourism Development Policy: Analysis of the Dynamics of Policy Content and Implementation Context - Heriyanto, Heriyanto; Fathonah, Iir Nikmatul; Harisal, Harisal; Litstiana, Yunika Depri; Damasinta, Alfiana (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
Border regions play a crucial role in strengthening national sovereignty and supporting development based on local potential. Sambas Regency, West Kalimantan, which borders Sarawak, Malaysia, prioritizes the tourism sector in its development plans. However, implementing tourism policies in this region has not been optimal. This study aims to analyze the implementation of tourism development policies in border areas using Merilee S. Grindle's policy implementation theory, which examines two main aspects: policy content and implementation context. The research approach used is qualitative with a case study, through in-depth interviews and document analysis. The research findings show that although the existing policies align with the direction of border area development, several issues have emerged in their implementation. There are gaps in the distribution of benefits, a lack of involvement from local stakeholders, and a mismatch between policy content and the implementation context. The main constraints identified are weak intersectoral coordination, low community participation, and limited institutional capacity. These findings suggest that successfully implementing border tourism policies requires governance based on collaboration and participation. Therefore, it is recommended to strengthen coordination among relevant sectors, enhance local community participation, and improve institutional capacity to support more effective policies.